2016
DOI: 10.1103/physrevb.93.085304
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of van der Waals interactions and lattice mismatch atMoS2/metalinterfaces

Abstract: We explore the adsorption of MoS2 on a range of metal substrates by means of first-principles density functional theory calculations. Including van der Waals forces in the density functional is essential to capture the interaction between MoS2 and a metal surface, and obtain reliable interface potential steps and Schottky barriers. Special care is taken to construct interface structures that have a mismatch between the MoS2 and the metal lattices of <1%. MoS2 is chemisorbed on the early transition metal Ti, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 70 publications
(158 reference statements)
7
88
0
Order By: Relevance
“…The extent of this interfacial interaction depends on whether the metal is physisorbed (i.e., weakly adsorbed) or chemisorbed (i.e., strongly adsorbed) on the MoS 2 surface, resulting in a small or large density of interface states, respectively. Moreover, the authors showed that by artificially enlarging the physical distance between MoS 2 and the metal, these interface states vanished [150]. Experimentally, this physical separation can be achieved by inserting suitable interfacial tunnel barriers or buffer layers in-between the MoS 2 and the contact metal (more on interfacial contact tunnel barriers is discussed in Section 8).…”
Section: The Schottky Barrier and The Van Der Waals (Vdw) Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of this interfacial interaction depends on whether the metal is physisorbed (i.e., weakly adsorbed) or chemisorbed (i.e., strongly adsorbed) on the MoS 2 surface, resulting in a small or large density of interface states, respectively. Moreover, the authors showed that by artificially enlarging the physical distance between MoS 2 and the metal, these interface states vanished [150]. Experimentally, this physical separation can be achieved by inserting suitable interfacial tunnel barriers or buffer layers in-between the MoS 2 and the contact metal (more on interfacial contact tunnel barriers is discussed in Section 8).…”
Section: The Schottky Barrier and The Van Der Waals (Vdw) Gapmentioning
confidence: 99%
“…This method, widely explored for engineering the contact resistivity in conventional 3D semiconductor FETs based on Si and Ge [226][227][228][229][230][231][232], is based on the incorporation of an ultra-thin insulating material (such as 2D hexagonal boron nitride or hBN, and oxides such as TiO 2 ) in-between the MoS 2 and the contact electrode, to effectively realize a metal-insulator-semiconductor (MIS) configuration at the contact. This thin interfacial insulating "buffer" layer in the MIS structure serves as a "Fermi level de-pinning (FLDP) layer" by increasing the physical separation between the MoS 2 and the contact electrode owing to its finite thickness, thereby, breaking or minimizing the metal/MoS 2 interfacial interaction responsible for the creation of mid-gap interface states that cause FLP [149][150][151]. Once this depinning is achieved, the contact work function can effectively be chosen to line up with or closer to the CBE or VBE of MoS 2 in accordance with the Schottky-Mott rule.…”
Section: Use Of Interfacial Contact "Tunnel" Barriersmentioning
confidence: 99%
“…We follow the strategy developed in Ref. [57] to define supercells and minimize strain, chosen to be applied to the metal slab because of the corresponding small effect on the electronic structure of the interface [25]. We develop the in-plane supercell lattice vectors T 1 = n 1 a 1 + n 2 a 2 and T 1 = Table 2: Parameters corresponding to the supercell construction of a Cu/MoTe 2 interface with minimal lattice mismatch (δ).…”
Section: Force Field Validation: Cu/mote 2 Interfacementioning
confidence: 99%
“…To gain better insight into the nature of these peaks, we examine the electronic structure of finite layer MoS 2 . Ignoring the effects of the van der Waals interaction with Au, 34 the band structure and DOS for 2 and 8 ML MoS 2 were calculated using DFT and are plotted in Figs. 4(a) and 4(b).…”
Section: Resultsmentioning
confidence: 99%